Hand grip strength test and its use in nutritional assessment - Schlüssel, M; Dos Anjos, L; Kac, G (2008)
This paper reviews the methodological and physiological aspects of hand grip strength measurement. Hand grip strength assesses skeletal muscle function and has received increasing attention from physicians and health-related researchers in the last years. Recently, it has deserved particular attention as an indicator of nutritional status, particularly in hospitalized patients. Sex, age, height, body mass and the dominant hand of the subjects are the main factors that influence the measure. The results of this review demonstrate that many other factors associated with the assessment protocol, such as the position of the individual, the type of instrument used, the number of measurements performed, the rest periods between measurements, the presence of verbal stimulation and a warm-up prior to the test can also influence the results. Therefore, it is important to develop a standardized protocol to improve the reliability of the measurements for this variable. Normative data for hand grip strength are still scarce and the literature still resents from the existence of reference values from population-based studies.